Systemic Poverty Modelling: Case of Central Asia - F. I. Arzhaev; V. Y. Andriukhin; D. V. Saprynskaya (Vestnik MGIMO-Universiteta)
Poverty is one of the most controversial issues in the academic discourse. The numerous theories and their different interpretations make theoretical approaches to poverty applicable to achieve different goals but not the one of its eradication. The politization of the problem and the motivation of political actors to harness the issue of poverty result in significant restrictions for objective assessment of the situation. Central Asia has been facing the problem of poverty for a long time, but this issue remains unresolved. The state of affairs differs a lot from one state to another in the region, however all of them are exposed to high risks since poverty in Central Asia has acquired the character of a systemic phenomenon. The abovementioned theses determine adaptation of the existing academic findings to regional specifics. The article hypothesizes that in Central Asian countries the factors of poverty persistence are linked to each other in vicious circles, the rupture of which is possible through systemic solutions in three public spheres – education, labor market and development institutions. To verify this hypothesis, the nature of poverty is put under test for consistency, the key characteristics of the problem for each of the Central Asian countries are highlighted. The major factors, contributing to the preservation of poverty are analyzed; the most important of them are revealed and logically connected to the three public spheres mentioned. The latter proves to be the most significant for the regional approach to poverty issues. The combination of statistical data, the poor quality of which represent a major limitation of the study, and the results of empirical conclusions has made it possible to identify the existence of two related “vicious circles” of poverty in the region – a vicious circle of factors of poverty persistence and a vicious circle of poverty and its consequences. Based on the data obtained through econometric modeling, a number of recommendations aimed at further reducing the severity of the problem in the Central Asian states have been developed. The proposed recommendations are formed considering the complexity and unrealizability of complex and simultaneous solutions to the problem of poverty and are designed to launch a mechanism for assessing the situation and its initial resolution.